Legal Analysis Of Licensing Authority In Space Utilization After The Work Copyright Law - Hanna Mariana Aritonang; Siti Nurhayati (Badan Penerbit STIEPARI Press, 2023)
The enactment of the Job Creation Law has created a lot of discussion about spatial law enforcement. This did not completely stop even after the issuance of Government Regulation (PP) No. 43 of 2021, which regulates the settlement of spatial discrepancies, forest areas, permits, and/or land rights. The spatial planning sector is quite complex when it comes to natural resources and environmental issues. Therefore, there needs to be synergistic collaboration among related parties, especially law enforcement. And there is an increase in the role of the region to provide support related to violations of space utilization that occur. The research used in this journal is normative legal research. There are already regulations that clearly regulate related to space or spatial planning that is still obeyed mainly from urban communities, as well as private parties who will build business locations (such as malls, plazas, and so on), as well as from governments in provinces, districts / cities can take action and carry out regulations that have been regulated. Remembering that the provision, utilization and sustainability of green open space in the future plays a big role in the ecosystem and preservation of nature with environmental aspects and with the renewal of licensing arrangements related to green open space in the perspective of the Spatial Planning Law and the Job Creation Law, it is clarified again and does not lead to the possibility of norm ambiguity or norm conflict.